THE INFLUENCE OF GENDER & INTELLECTUALLY REPETITION (AIR) AUDITORY LEARNING MODELS ON STUDENT LEARNING OUTCOMES - Mohammad Archi Maulyda; Umar Umar; Asrin Asrin; Vivi Rachmatul Hidayati; Awal Nur Kholifatur Rosyidah (Jurnal Karya Pendidikan Matematika, 2020)
In this study, we want to know the effect of the Auditory Intellectual Repetition (AIR) learning model. In this study using a quantitative approach, with a Pre-Experimental Design research design with the type of One-Group Pretest-Posttest Design, where student learning outcomes will be reviewed in terms of student pre-test and post-test scores. Based on the analysis of research data, the average pre-test student learning outcomes are 40.94 and the average post-test student learning outcomes are 83.28. From these data, an analysis of Paired Sample t-Test data was performed, and the value of the calculated t-≤ t-table (7.758 <8.281) was calculated using the Sig. (2-tailed) of 0,000 then H0 is accepted. The conclusions of this study are (1) Student learning outcomes before the treatment is lacking, (2) Student learning outcomes after treatment is good, (3) There is a positive influence from the use of the Auditory Intelectual Repetition (AIR) learning model.